Cross sectional study on relationship between plasma homocysteine levels with degree of sensorineural hearing loss - Raja Lope Ahmad, Raja Ahmad Al'konee; Ayob, Azizi; Wan Leman, Wan Ishlah; Mokhtar, Rafidah Hanim (Springer, 2007)
OBJECTIVES: Sensorineural hearing loss (SNHL) is one of common clinical problem presented in daily otological practice. The pathological problems can be either in the cochlea or in the retrocochlear region. Majority of the aetiologies are unknown. The causes have been postulated secondaries to vascular pathology, autoimmune reaction, inflammatory process due to viral or bacterial infection, aging process (presbyacusis), head trauma etc. Nevertheless majority of researchers postulated that compromised cochlear blood flow has been considered to be a principal aetiologic factor causing sensorineural hearing loss. Hyperhomocysteinaemia have been found to be associated with vascular diseases such as cerebral vascular accident, peripheral vascular disease, coronary arterial disease, renal disease and dementia. The fact that homocysteine play an important role in vascular diseases and in the involvement of the pathogenesis of atherosclerotic plaque, there are possibilities that it may have an association with the aetiopathological in sensorineural hearing loss. This association however remained to be established. Currently there were no reported studies pertaining to the association between plasma homocysteine levels with the degree of sensorineural hearing loss.